Breeding erect plant type sweetpotato lines using cross breeding and gamma-ray irradiation - Kuranouchi, Toshikazu (Breeding science, 2016)
Few sweetpotato (Ipomoea batatas Lam.) cultivars with erect plant type are available despite their advantages over spreading type, such as simplicity of cultivation and ability to adapt to limited space. One of the reasons is insufficiency of their agronomic characteristics for table use. So, it is important to overcome these drawbacks of ER-type lines. We attempted to breed new erect plant type sweetpotato lines having good agronomic traits using cross breeding and mutation breeding with gamma-ray irradiation. With cross breeding we successfully developed new erect plant type lines with almost equal levels of yield as compared to 'Beniazuma', one of the leading cultivars in Japan. However, mutation breeding failed to develop any promising lines because we could not obtain distinct erect plant type lines. In the future larger numbers of plants should be used for mutation breeding, and irradiation methods should be improved